2021
DOI: 10.1088/1742-6596/1782/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the geometry of defects in textronic structures on their electrical properties

Abstract: Continuity of the conductive path is a prerequisite for the phenomenon of electric current to exist in the structures of wearable electronics. The value of the current depends not only on the material properties of the structure but also on the geometrical dimensions of the defect of a thin electrically conductive layer. The article describes the analysis of the influence of the width and slope of the linear defect of a thin metallic layer on the value of the current. The conducted simulations show that when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As it results from the precise analytical solution described in [12,13] for a single defect with the shape of a rectilinear segment, the current density at its ends assumes infinite values (despite the continuity of the potential). It was shown in [32] that this effect can introduce a significant error in the calculation of the total current flowing in the conducting stripe (Figure 2) only when the length of the defect is close to the width of the stripe and when at least one of its ends is at a distance comparable to the width of the defect. In this paper, the impact of defects with lengths much smaller than the stripe sizes is analyzed, and it was concluded that modeling them as infinitely thin does not significantly affect the simulation results.…”
Section: Description Of the Model And Formulation Of The Problemmentioning
confidence: 99%
“…As it results from the precise analytical solution described in [12,13] for a single defect with the shape of a rectilinear segment, the current density at its ends assumes infinite values (despite the continuity of the potential). It was shown in [32] that this effect can introduce a significant error in the calculation of the total current flowing in the conducting stripe (Figure 2) only when the length of the defect is close to the width of the stripe and when at least one of its ends is at a distance comparable to the width of the defect. In this paper, the impact of defects with lengths much smaller than the stripe sizes is analyzed, and it was concluded that modeling them as infinitely thin does not significantly affect the simulation results.…”
Section: Description Of the Model And Formulation Of The Problemmentioning
confidence: 99%